Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Ekstrinsik terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening ada PT. Bangun Beton Indonesia - Raras Yulia Askar; Wawan Prahiawan; Enis Khaerunnisa (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to test and analyze the influence of Transformational Leadership Style and Extrinsic Motivation on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Build Concrete Indonesia. The method used in this research is quantitative with a sampling technique using the census method with a saturated sampling type totaling 81 respondents. In the data analysis technique, using a model test with the SmartPLS 4.0 analysis tool which consists of an outer model and an inner model. The results of this research show that: 1) Transformational Leadership Style has a positive and significant effect on Employee Performance, the results of t-count > t-table (3,082 > 1.96) and significance level < 0.05 (0.002 < 0.05). 2) Extrinsic Motivation has a positive and significant effect on Employee Performance with the results of t-count > t-table (2,646 > 1.96), and a significance level < 0.05 (0.008 < 0.05). 3) Transformational Leadership Style has a positive and significant effect on Job Satisfaction, the results of t-count > t-table (3,217 > 1.96) and significance level < 0.05 (0.001 < 0.05). 4) Extrinsic Motivation has a positive and significant effect on Job Satisfaction with the results of t-count > t-table (4,149 > 1.96), and a significance level < 0.05 (0.000 < 0.05). 5) Job satisfaction has a positive and significant effect on employee performance with the results of t-count > t-table (4,013 > 1.96), and a significance level < 0.05 (0.000 < 0.05). 6) Job Satisfaction is able to mediate the relationship between Transformational Leadership Style and Employee Performance with the results of t-count > t-table (2,533 > 1.96), and a significance level < 0.05 (0.011 < 0.05). 7) Job Satisfaction is able to mediate the relationship between Extrinsic Motivation and Employee Performance with the results of t-count > t-table (2,589 > 1.96), and a significance level < 0.05 (0.010 < 0.05).